Changes In The Physical Properties Of Previously Irrigated Light Sandy Meadows And Newly Irrigated Soils Of Mirzachol Under The Influence Of Deflation - Umarov Muxammad Ismatullayevich; Xoliqov Xosilbek Abduraxmon O‘g‘li; Boboqulova Munira Shuhrat qizi; Xudoyqulova Oltinoy Po‘lat qizi; Ibragimov Dilmurod Ziyodullajon o‘g‘li (Zien Journals, 2024)
The article presents changes in the physical properties of old-irrigated light sandy meadows of Mirzachul and newly irrigated soils under the influence of deflation, the results of monitoring various deflationary processes on irrigated lands. Experiments were carried out. It is recommended to plant strip crops as agricultural crops to restore, increase and protect the fertility of wind-eroded soils.
Keywords: Moisture retention and water content of soil; wind erosion; strip crops; soil fertility